Absence of short-term changes in knowledge and attitudes among household contacts of COVID-19 cases during the post-acute phase of the pandemic in Catalonia and Navarre, Spain - Bullón-Vela, Vanessa; Toledo, Diana; Echeverría, Aitziber; Godoy, Pere; Cenoz, Manuel García; Parrón, Ignasi; Castilla, Jesús; Domínguez, Angela; Martínez-Baz, Iván (Frontiers in Public Health, 2024)
SARS-CoV-2 has shown high transmissibility within the population, especially in the household setting where transmission rates are generally higher as there is more intense and/or repeated exposure. In this context, having correct knowledge, and positive attitudes towards the COVID-19 disease and its preventive measures is of crucial importance. However, these factors can be seen to change over time. In this original article, we used a telephone survey conducted in two distinct regions in Spain to evaluate short-term changes in knowledge and attitudes relative to COVID-19 disease and its preventive measures in household contacts of active cases, in the post-acute phase of the pandemic. The study also evaluated the information sources habitually used by these contacts and measured their changes over time. We found that household contacts had generally maintained adequate knowledge and correct attitudes during the post-acute phase of the COVID-19 pandemic in Spain. Given the current situation relative to the disease, our findings provide insights that will allow researchers, public health programmers, and policymakers to compare changes over time and implement targeted strategies for the general public and vulnerable groups.